A novel double-antibody sandwich ELISA based on monoclonal antibodies against the viral spike protein detects porcine deltacoronavirus infection - Yingjie Bai; Ruiming Yu; Guangqing Zhou; Liping Zhang; TianTian Wang; Ya Liu; Dongsheng Wang; Zhongwang Zhang; Yonglu Wang; Huichen Guo; Li Pan; Xinsheng Liu (Microbiology Spectrum)
ABSTRACT Porcine deltacoronavirus (PDCoV) is a significant emerging pathogen that causes severe enteric disease in swine, and therefore significant economic losses in the pig farming industry. Here, we developed a novel double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) based on two monoclonal antibodies directed against the PDCoV spike protein. These two monoclonal antibodies were obtained through hybridoma fusion and screening, and they can specifically react with the PDCoV spike protein. The detection limits of the DAS-ELISA for the recombinant spike protein and viral titer were approximately 0.12 ng/mL and 1.96 × 10³ copies/μL, respectively. The DAS-ELISA did not cross-react with other swine enteric coronaviruses, including porcine epidemic diarrhea virus, transmissible gastroenteritis virus, or porcine rotavirus. A total of 145 rectal swab samples were collected and tested for the presence of PDCoV with the DAS-ELISA and reverse transcription-quantitative PCR (RT-qPCR). The coincidence rate between the DAS-ELISA and RT-qPCR was 91.03%, with a kappa value of 0.814, indicating that the DAS-ELISA is a reliable method for viral antigen detection in clinical samples. DAS-ELISA had a sensitivity of 92.85% and a specificity of 89.89%. The positive predictive value and negative predictive value of this method are 85.25% and 95.24%, respectively. Furthermore, the DAS-ELISA can also be used to detect the spike protein in PDCoV vaccines, making it a valuable tool for assessing the efficacy of PDCoV vaccines.IMPORTANCESince 2014, porcine deltacoronavirus (PDCoV) has spread widely across multiple countries and regions, causing significant economic losses to the global livestock industry. Currently, no commercially available vaccine exists for the prevention of PDCoV infection; therefore, accurate and effective diagnostic methods are crucial for its control and prevention. In this study, the PDCoV S protein expressed in Chinese Hamster Ovary (CHO) cells was used to immunize mice, and a novel double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) was established based on two monoclonal antibodies. The DAS-ELISA had high sensitivity, good repeatability, strong specificity, and high consistency for detecting clinical samples and spike protein in PDCoV vaccines. Therefore, the DAS-ELISA established in this study may be a reliable and effective tool for detecting PDCoV infection and the efficacy of PDCoV vaccines.